Does Halal Poultry Matters? An Assessment among Generation Y Non-Muslim Confidence and Choice in Malaysia - Kit Teng, Phuah; Lim Jit Heng, Bernard; Intan Nurdiana Wong Abdullah, Siti (International Journal of Psychosocial Rehabilitation, 2020)
Purpose of Study: The "halal" term stands a significant importance for Muslim consumers in their daily life especially when it relates to food products. With the majority of the population in Malaysia is Muslim consumers, most of the food products will need to have halal certification. However, some concerns from the nonMuslim consumers exist as they do not fully understand the halal concept as well as the importance of halal certification in food supply chain. As such, this research is important to halal literature as there are limited studies on Gen-Y Non-Muslim consumers and halal poultry. The purpose of this research is to assess the Gen-Y Non Muslim consumers’ confidence and choice criteria towards halal poultry.Methodology: A study was conducted in Malaysia where 475 Gen-Y Non-Muslim consumers were surveyed using structured questionnaires. The Howard and Sheth Model was adopted and modified in this study along with structural equation modeling to analyze the collected data.Result: The results indicated that stimulus ambiguity, attention and brand comprehension will impact Gen-Y Non-Muslim consumers’ confidence level towards Halal poultry. On the other hand, variables like consumers’ motive, attitude and confidence level will influence Gen-Y Non-Muslim consumers’ choice in choosing Halal or nonHalal poultry.